TIME-SERIES ANALYSIS OF SATELLITE-BASED TRACE GASES CONCENTRATIONS IN PORT AREAS IN THE PHILIPPINES USING SENTINEL-5P - L. A. Aporto; M. Latunio; R. V. Ramos; A. M. Tamondong (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
This study examined the temporal variations of Nitrogen Dioxide (NO2) and Sulfur Dioxide (SO2) concentrations retrieved from Sentinel-5P TROPOMI in six port areas in the Philippines, representing different climate types. The results demonstrate that the COVID-19 lockdowns led to a significant decrease in NO2 levels, while SO2 concentrations varied due to factors such as volcanic activity. Seasonal analysis of NO2 and SO2 retrievals, considering the four climate types in the Philippines, revealed that the wet season values for both pollutants were higher than the dry season values for most ports. This disparity contradicted the general trend of higher air pollutant levels during the dry season and lower levels during the wet season. The authors attributed this to the nature of port activities during inclement weather, where ships are more likely to be docked with continuously operating engines, leading to continuous emissions within the port buffer zones. Temporal analysis and time series decomposition analysis revealed patterns and trends, identifying the months of minimum and maximum pollutant concentrations and the overall trend throughout the study period.